Development of Two-Dimentional Geometry Module based on APOS Theory for 4th Grader Students - Dewi Trisnawati; Kristi Liani Purwanti; Ahmad Faridh Ricky Fahmy (EduMa: Mathematics education learning and teaching, 2022)
This study aims to produce two-dimentional geometri module based on the APOS theory for 4th grader students is valid and feasible. This research method is research and development (R&D) using a 4D development model (define, design, develop, and disseminate). However, in this study, the 3-D development was modified, namely the disseminate stage was not carried out due to limited time, energy, and cost in carrying out this research. The subject of this research is the 4th grader of Semarang State Islamic Elementary School (MIN Semarang). Based on the results of the study, it was found that (1) module assessment by material and media expert the quality of the module quality by material and media expert validators is in the very good category with a value of 4,7 and 4,4. (2) Student learning outcomes from field trials obtained an average of 79,8 with a completeness level of 78.6%. It can be concluded that the product of two-dimentional geometri module based on the APOS theory is valid and feasible for use in learning